PENINGKATAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK - nofriyanti nofriyanti (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The background of this research is the low student learning outcomes caused by an inappropriate learning approach. The process carried out in class is also less enjoyable, causing the learning outcomes and learning process of students in class IX SPM Negeri 04 Bungo. So with this problem, the researchers conducted research using the Talking Stick model. This type of research is classroom action research which consists of four stages, namely planning, action, observation and reflection, which is carried out collaboratively between practitioners and observers. The research was conducted at SMPN 04 Bungo. The subjects of this study were 36 students of class IX.5. The research was carried out for 2 cycles. Each cycle consists of 2 meetings. The results of the research are: 74.07 in the first cycle to 78.32 in the second cycle 1 so the Talking Stick model can improve student learning outcomes.